Improvements in antioxidant status after agraz consumption was associated to reductions in cardiovascular risk factors in women with metabolic syndrome (2021)
ABSTRACT: In this study were evaluated the effects of the chronic consumption of agraz (Vaccinium meridio-nale) on antioxidant status and oxidative stress markers in 40 women with metabolic syndrome(MetS) (47.2 ± 9.4 years) through a double-blind, crossover design study, in which participants consumed daily agraz or placebo during 4 weeks, separated by a 4-wk washout period. At the end of each intervention period, endogenous antioxidant enzymes activity, serum total antioxidant capacity (TAC) (ferric reducing ability of plasma [FRAP]; Oxygen Radical Absorbance Capacity[ORAC] and 2,2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) [ABTS]), and oxidative stress markers (Oxo-2ʹ-deoxyguanosine (8-OHdG) and F2-isoprostane) were determined. Women who increased endogenous antioxidant enzymes activity and serum TAC after agraz consumption,compared to placebo, significantly reduced oxidative stress markers, total cholesterol, LDL-cho-lesterol (LDL-c) levels, and waist circumference, demonstrating beneficial effects in the group of women in whom antioxidant parameters increased after agraz consumption, evidencing an individual variability in response to the beverage consumed.